Many-body physics in two-component Bose–Einstein condensates in a cavity: fragmented superradiance and polarization. (15th May 2018) - Lode, Axel U J; Diorico, Fritz S; Wu, RuGway; Molignini, Paolo; Papariello, Luca; Lin, Rui; Lévêque, Camille; Exl, Lukas; Tsatsos, Marios C; Chitra, R; Mauser, Norbert J
Abstract: We consider laser-pumped one-dimensional two-component bosons in a parabolic trap embedded in a high-finesse optical cavity. Above a threshold pump power, the photons that populate the cavity modify the effective atom trap and mediate a coupling between the two components of the Bose–Einstein condensate. We calculate the ground state of the laser-pumped system and find different stages of self-organization depending on the power of the laser. The modified potential and the laser-mediated coupling between the atomic components give rise to rich many-body physics: an increase of the pump power triggers a self-organization of the atoms while an even larger pump power causes correlations between the self-organized atoms—the BEC becomes fragmented and the reduced density matrix acquires multiple macroscopic eigenvalues. In this fragmented superradiant state, the atoms can no longer be described as two-level systems and the mapping of the system to the Dicke model breaks down.